The Effect of Capital Access, Financial Management, and Optimization of BUMDes Utilization on BUMDes Income - Syarifah Aini; Endang Sri Wahyuni (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of capital access, financial management, and optimization of Village-Owned Enterprises (BUMDes) on BUMDes income in Bengkalis District and Bantan District. This study uses a quantitative approach with a survey method, where primary data is collected through the distribution of questionnaires to BUMDes administrators and managers and analyzed using multiple linear regression with the help of the SPSS program. The results show that, partially, access to capital has a positive and significant effect on BUMDes income (t = 7.946; Sig. < 0.001) and the optimization of BUMDes utilization also has a positive and significant effect (t = 4.215; Sig. < 0.001), while financial management has a significant negative effect (t = -4.290; Sig. < 0.001). Simultaneously, access to capital, financial management, and optimization of BUMDes utilization have a significant effect on BUMDes income (calculated F > table F; Sig. < 0.001), which shows that increasing BUMDes income requires synergy between the availability of capital, effective financial management, and optimal utilization of assets and business units.